Penerapan Akulturasi Budaya pada Bentuk dan Struktur Masjid Agung Surakarta - Leny Pramesti; Untung Joko Cahyono; Musyawaroh Musyawaroh (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2025)
The Application of Cultural Acculturation to the Form and Structure of the Surakarta Grand MosqueThe architecture of the Surakarta Grand Mosque is a physical manifestation of cultural acculturation, integrating Islamic values, Javanese cosmology, and historical development. This study aims to identify the application of cultural acculturation within the mosque’s spatial layout, form, and structure. Utilizing a qualitative method with asingle case study approach, the research employs interactive analysis through field observations, interviews, and historical document reviews spanning the reigns of Paku Buwana III to Paku Buwana X. Results indicate that spatially, the mosque consistently applies a Javanese-Islamic cosmological axis aligned with Demak Palace patterns. In terms of from and structure, visual hybridity is found in the tiered tajug roof and thesakaguru timber construction system, which adapted to functional and ceremonial need. These findings confirms that cultural acculturation in the Surakarta Grand Mosque serves as a strategy that strengthens the resilience of vernacular architecture against changing times without losing its philosophical identity.